2007
DOI: 10.1002/art.22924
|View full text |Cite
|
Sign up to set email alerts
|

Rate and determinants of progression of atherosclerosis in systemic lupus erythematosus

Abstract: Objective. To determine the rate of atherosclerosis progression as well as the relationship of traditional risk factors, systemic lupus erythematosus (SLE)-related factors, and treatment to atherosis progression in SLE patients.Methods. Outpatients in the Hospital for Special Surgery SLE Registry underwent serial carotid ultrasound and clinical assessment in a longitudinal study.Results. Among 158 patients, 77 (49%) had persistent absence of atherosclerosis (carotid plaque), 36 (23%) had unchanged atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
128
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 43 publications
11
128
3
4
Order By: Relevance
“…61 Atherosclerosis progresses at twice the rate seen in non-SLE populations; rate of progression is directly related to duration of disease and homocysteine levels. 62 Similar considerations regarding preventive and screening strategies as discussed in the RA section apply to patients with SLE. …”
Section: Atherosclerosismentioning
confidence: 99%
“…61 Atherosclerosis progresses at twice the rate seen in non-SLE populations; rate of progression is directly related to duration of disease and homocysteine levels. 62 Similar considerations regarding preventive and screening strategies as discussed in the RA section apply to patients with SLE. …”
Section: Atherosclerosismentioning
confidence: 99%
“…Determinants of atherosclerotic progression after multivariate analysis were patient age at diagnosis, disease duration, and baseline homocysteine concentration. Lupus patients with stable plaque and progressive plaque were different only in baseline homocysteine concentration (Roman, Crow et al 2007). A recent study by Perna et al implied a relationship of both asymmetric dimethylarginine and homocysteine to arterial stiffness, but not to the presence or extent of carotid atherosclerosis (Perna, Roman et al 2010).…”
Section: Slementioning
confidence: 99%
“…An inverse relationship between SLE activity and plaque size was reported by Manzi et al and longer disease duration was independently associated with carotid plaque (Manzi, Selzer et al 1999) and coronary calcium scores (Von Feldt, Scalzi et al 2006). In a cross-sectional and in a longitudinal study, Roman et al found that longer disease duration and higher Systemic Lupus International Collaborative Clinics (SLICC) damage index were independent predictors of carotid plaque formation (Roman, et al 2003;Roman, et al 2007). In another report, SLE specific variables were associated with aortic stiffness and included older age, hypertension, higher C3 levels, lower white blood cell count, higher insulin levels, and renal disease (Selzer, Sutton-Tyrrell et al 2004).…”
Section: Slementioning
confidence: 99%
“…As in rheumatoid arthritis, patients with systemic lupus erythematosus also have an increased risk of atherosclerosis [29][30][31][32][33][34][35]. The highest risk group is young females with 2-fold increase in atherosclerosis above the general population [29,[35][36][37].…”
Section: Atherosclerosismentioning
confidence: 99%